Perlukah Akta Notaris Ditanda Tangani Bersamaan? - Tandiari, Samuel; Sitorus, Winner; Aswan, Muhammad (Universitas Widya Gama Malang, 2024)
This study aims to evaluate and The notary public are forbidden to sign consecutively and to evaluate and analyze the legality and legal certainty of the date of notarial deed signed not simultaneously by the appearers. This research is a type of empirical research, the location of this research was conducted in Makassar City and North Toraja Regency, South Sulawesi Province. The research results show that. The legal implication of signing a notary deed that is not carried out simultaneously by the appearers before a Notary is that it can degrade the authentic deed made by the Notary into an underhanded deed as referred to in Article 16 paragraph (1) letter m, paragraph 9 jounto Article 44 UUJN. Because the signing of the deed simultaneously by the parties, witnesses, and the Notary is an obligation required by UUJN. So that if this is not done, it will result in an authentic deed made by the Notary being defective from the way the deed is made and becomes a deed under the hand. And the legality and legal certainty regarding the date of notarial deed that was not signed simultaneously by the appearers is that a notary should also be aware that the product of the deed is interpreted as an effort by the state to create legal certainty and protection for the general public. So that the negligence and mistakes made by the Notary will result in the degradation of the authentic deed he made into a private deed so that he can be subject to civil liability, where the party who suffers a loss can demand reimbursement of costs, compensation and interest from the Notary concerned.